2013
DOI: 10.1016/j.scijus.2012.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Determining the order of deposition of natural latent fingerprints and laser printed ink using chemical mapping with secondary ion mass spectrometry

Abstract: , "Determining the order of deposition of natural latent fingerprints and laser printed ink using chemical mapping with secondary ion mass spectrometry" Science and Justice 53 (2003) AbstractTime-of-flight secondary ion mass spectrometry (ToF-SIMS) chemical mapping was used to investigate the order of deposition of natural latent fingerprints and laser printed ink onpaper. This feasibility study shows that sodium, potassium and C 3 H 5 positive ions were particularly abundant endogenous components of the na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…Bradshaw et al investigated the effect on fingerprint analysis when it is on a lifting tape or on deposition surface. Using MALDI‐MS, they have found that it is preferable to prioritize printing on the deposition surface, even though it is possible to do analysis in both cases ().…”
Section: Resultsmentioning
confidence: 99%
“…Bradshaw et al investigated the effect on fingerprint analysis when it is on a lifting tape or on deposition surface. Using MALDI‐MS, they have found that it is preferable to prioritize printing on the deposition surface, even though it is possible to do analysis in both cases ().…”
Section: Resultsmentioning
confidence: 99%
“…A question that is sometimes posed when fingermarks are developed on an incriminating document is whether the paper was handled before or after the incriminating content was present. This issue has been addressed by several researchers using SIMS (Attard‐Montalto et al, 2014; Attard‐Montalto, Ojeda, & Jones, 2013; Bailey et al, 2010; Bright et al, 2012), with the general approach being to identify signals from chemical species unique to both the ink and fingermark components. It has been demonstrated that it is possible to discriminate between the “ink over fingerprint” and “fingerprint over ink” scenarios using both imaging and depth profiling modes prior to development of the fingermark.…”
Section: Utilization Of Fingermark Chemistry To Obtain Additional Contextual Informationmentioning
confidence: 99%
“…Improving biometric detail of the ridge structure, through developing novel formulations for fingermark development for example powders from quantum dots, new solvents, and micronized powders [26,53,57], studying interactions on complex surfaces and between sequential processes [51,54,55]. A separate area seeks to gain also additional information from the suspect, such as gender and drug use to add to the suspect profile [71,72,74,77] or to improve understanding of the forensic scene or timeline [54,68,69,75,76].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, AFM and SEM can provide some information particularly with aid to the identification of the chronology of documents. Kasas et al [65] use these techniques to identify ball-point pen ink above a layer of printing, Watson & Watson [67] use AFM to explore ball point pen lines crossing each other, and overlapping fingermarks, though limit the substrate to smooth [68,69] and Bailey et al [69,70] use SEM to examine paper and printing structure, and identify ToF-SIMS as an analytical tool to assess whether printing is above or below a fingermark, by for example, the presence and distribution of sodium in the top surface of the document. The texture of the laser printed surface is shown in figure 9.…”
Section: Fingermark -Surface Interactionmentioning
confidence: 99%